(untitled) (DAPesquisa, 2020)
Two writings constitute this text. The first one is colorful, narrates the weaknesses and insecurities of the writing process. The second one is an academic paper that discusses two research practices in art– perfography (perfografia) and situated writing in relation with the Modus Operandi AND. Both have the cartographic attitude – careful perception of processes and openness to embrace events – as a principle of action.